A Social Media Intervention for Promoting Oral Health Behaviors in Adolescents: A Non-Randomized Pilot Clinical Trial - Susana J. Calderon; Carissa L. Comnick; Alissa Villhauer; Teresa Marshall; Jan-Ulrik Dahl; Jeffrey A. Banas; David R. Drake (MDPI AG, 2023)
Poor oral hygiene and excessive consumption of soda are among the main drivers of systemic health issues in adolescents in the United States. This non-randomized pilot clinical trial focused on the effects of a health text message system and smartphone-based intervention on adolescent tooth-brushing behavior and dietary choices, with a convenience sample of 94 participants aged 12 to 14 years old. A group of 75 participants agreed to use a tooth-brushing app and received a health text message; the other group of 15 agreed to use the tooth-brushing app, but did not receive a health text message. Saliva specimens were collected directly before and at the end of each experiment; changes in the salivary presence of cariogenic bacteria over the duration of the study were evaluated and compared with the demographics and behavioral variables. Within the text message group, 5% of participants increased the frequency of daily tooth brushing. Within the non-intervention group, 29% of participants increased the frequency of their daily tooth brushing. There were reductions in the total salivary bacteria and total streptococci in both groups (p < 0.001), but no change in the presence of cariogenic Mutans streptococci. Raising adolescents' consciousness of oral health behavior resulted in marginal to moderate improvements to oral hygiene and dietary choices, as well as reductions in total salivary bacteria.